2019
DOI: 10.1021/acsabm.9b00345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Regeneration Potential of Long-Term Soaked Natural Hydroxyapatite

Abstract: Natural hydroxyapatite (HA) was derived from pig bones (PBs) for tissue engineering applications through heat treatment. Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), X-ray fluorescence (XRF), energy-dispersive Xray spectroscopy (EDX), and field emission scanning electron microscopy (FE-SEM) were employed for the analysis of heat-treated PB powder. In addition, inductively coupled plasma (ICP) mass spectroscopy was applied to examine the phase organizations and chemical composition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The XRD pattern resembled the previously reported pattern of HAp, indicating that heat treatment facilitates the formation of natural HAp from human teeth [27]. The XRD peak at 2θ = 33.3° suggested the existence of the CaP moiety in developed bioceramics [28]. The presence of the different functional groups in bioceramics was examined through the FTIR spectroscopy.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The XRD pattern resembled the previously reported pattern of HAp, indicating that heat treatment facilitates the formation of natural HAp from human teeth [27]. The XRD peak at 2θ = 33.3° suggested the existence of the CaP moiety in developed bioceramics [28]. The presence of the different functional groups in bioceramics was examined through the FTIR spectroscopy.…”
Section: Resultssupporting
confidence: 82%
“…Human teeth (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) were received from the Department of Oral and Maxillofacial Surgery, Dental Hospital, Seoul National University, Republic of Korea. All procedures for teeth handling were performed under the regulation of an experimental protocol permitted by the Institutional Review Board (IRB) of the Dental Hospital, Seoul National University, Seoul, Korea (IRB No.…”
Section: Preparation Of Nano-calcium Phosphate Bioceramicmentioning
confidence: 99%
“…In dental and orthopaedic surgery, various ceramics have been used to fill bone defects and to cover metallic implant surfaces to improve the integration of implants with the host bone. However, their clinical tissue engineering applications have been limited due to their fragility, implantation shaping difficulty and the new bone formed in a porous HAP network cannot sustain the mechanical load needed for remodeling [13,14].…”
Section: Biomaterialsmentioning
confidence: 99%
“…The mechanism is associated with the formation of the apatite layer, due to the partial dissolution of HAP and ion exchanges between SBF solution and HAP surface. Antibiotic, anti-cancer, and gene therapy delivery vehicles are among the applications of HAP scaffolds due to their ability to dissolve slowly at the target site [13,31].…”
Section: Biological Properties Of Hapsmentioning
confidence: 99%
“…1−3 Previously, it has been reported that primarily HA (Ca 1 0 (PO 4 ) 6 (OH) 2 ) and β-tricalcium phosphate (Ca 3 (PO 4 ) 2 ) (β-TCP) made up ∼93 and ∼7 wt %, respectively, of sintered bone powder. 4 Calcium phosphate (Ca−P) is the key constituent of HA and is essentially involved in rapid regeneration of the desired bone tissue. 4 Ca−P exhibits substantial bioactivity and osteoconductivity during in vitro and in vivo studies, as it has the potential to form biological bone equivalents, even without calcium-deficient carbonate apatite.…”
Section: Introductionmentioning
confidence: 99%